Sinkretisme Siwa Budha dalam Lontar Candra Bhairawa - I Made Dian Saputra; I Nyoman Suarka (Universitas Udayana, 2018)
Candra Bhairawa manuscript is a classical literary work which is full of knowledge. It is selected as the object of this study, aimed at a deeper investigation of the meanings of Hinduism teachings in said literary work. Furthermore, this study on Candra Bhairawa manuscript also aimed at identifying the aspects of Siwa-Buddha Ta wa. The Syncretism of Siwa and Buddha has become a way of life, which in turn gave birth to several literary works that have become moral guideline for literary enthusiast in the archipelago. The Hermeneutics theory was used to analyze the aspects of meanings of the text in Candra Bhairawa manuscript. The study shows that the Candra Bhairawa manuscript was based on two contrasting basic conceptions of Siwa and Buddha, which formed a balance aiming at a mutual goal of the deliverance of the soul from worldly ties, known as Moksa. In order to achieve said state, one must go through several stages known as sanyasa, namely the Yoga Sanyasa and the Karma Sanyasa.